The model for regulating press coverage that applies the principle of presumption of innocence - Mustawa Mustawa (Indonesia Prime, 2019)
The Journal examines the need for harmonization of the Press news, wrote legal news, and Stándar the journalist's profession in the press law. This harmonization intended so that among material, the one with other material can complement each other to respect the principle of presumption not guilty. The purpose of the law not void because things or circumstances are not regulated in the PressLaw, or even if it governs by a statute but is unclear or even incomplete. The vacancy of the law eventually raises the legal uncertainty (Rechtsonzekerheid), which further raises the legal mess (rechtsverwarring). This uncertainty of the law, so that the knowledge of the law Adequate does not support journalists who write Legal news, and the professional standards of journalists use different recruitment criteria. Consequently, it has been difficult to Create a responsible press.